Anthracene functionalized terpyridines – synthesis and properties - Wehmeier, Falk; Mattay, Jochen (Beilstein Journal of Organic Chemistry, 2010)
The synthesis of several symmetrically 4,4″-functionalized 2,2′:6′,2″-terpyridines is reported. In addition to the biscarboxylic acid 4,4″-tpy(CO2H)2 (3), the anthryl esters 4,4″-tpy(CO2CH2Anth)2 (5a) and 4,4″-tpy(CO2CH2CH2OAnth)2 (5b) were synthesized. Furthermore, both anthryl esters were used to synthesize symmetric iron(II)-bis(terpyridine)complexes 6a–b. Irradiation experiments were carried out with both the free ligands and an iron(II)-complex in order to investigate the photochemistry of the compounds.
Keywords: anthracene; coordination chemistry; photochemistry; terpyridine